PENANAMAN DAN PENGEMBANGAN KARAKTER PEDULI LINGKUNGAN DI SEKOLAH ALAM (STUDI KASUS DI SMP ALAM AR-RIDHO SEMARANG) (Journal of Biology Education, 2014)
Abstract__________________________________________________________________________Nature of school Ar-Ridho Semarang is a school that has been professionally managed vision caring environment. character education. The concept of learning in the School of Natural-based natural environment, so the environment is the key to successful learning. Therefore, the value of environmental care is one of the main characters that must be instilled and developed in the school of nature as a special character school. The purpose of this study is to analyze how the investment value of environmental care on the biology of learning as well as the development matter environment value beyond learning biological in SMP Alam Ar-Ridho. The research method used is a qualitative study of naturalistic descriptive exploratory method. Based on the results of the data analysis and discussion, it can be concluded that the cultivation and development of environmentally conscious character in SMP Alam Ar-Ridho implemented through structured activities outside lessons. Planting and caring character development environment made ​​regarding the establishment of the mindset of students through environmental education integrated in regular school activities. Planting and development of caring character environment with the formation mindset shown to form student of SMP Alam Ar-Ridho  religious character, independent, responsible, and creative. Abstrak ____________________________________________________________________________ Sekolah alam Ar-Ridho Semarang merupakan sekolah yang telah dikelola secara profesional memiliki visi pendidikan karakter peduli lingkungan. Konsep pembelajaran di Sekolah Alam berbasis lingkungan alam sekitar,  sehingga lingkungan adalah kunci dari keberhasilan pembelajaran. Oleh karena itu, nilai peduli lingkungan merupakan salah satu karakter pokok yang harus ditanamkan dan dikembangkan di sekolah alam. Tujuan dari penelitian ini adalah untuk menganalisis bagaimana penanaman karakter peduli lingkungan pada pembelajaran biologi serta pengembangan karakter peduli lingkungan di luar pembelajaran biologi di SMP Alam Ar-Ridho. Metode penelitian yang digunakan merupakan penelitian kualitatif naturalistik menggunakan metode deskriptif eksploratif. Berdasarkan hasil analisi data dan pembahasan dapat ditarik kesimpulan bahwa penanaman dan pengembangan karakter peduli lingkungan di SMP Alam Ar-Ridho dilaksanakan melalui kegiatan-kegiatan terstruktur di luar pembelajaran. Penanaman dan pengembangan karakter peduli lingkungan dilakukan dengan membentukan mindset siswa melalui pendidikan lingkungan hidup yang terintegrasi pada kegiatan rutin sekolah. Penanaman dan pengembangan karakter peduli lingkungan dengan pembentukan mindset terbukti dapat membentuk siswa SMP Alam Ar-Ridho yang berkarakter religius, mandiri, bertanggung jawab, dan kreatif.